WORK RELATED MUSCULOSKELETAL DISCOMFORT (WRMSD) AMONG PHYSIOTHERAPISTS (International Journal of Physiotherapy, 2014)
Background: Physiotherapists are known to incline work related musculoskeletal distress. In work put, the health awareness experts are defenseless against supporting the musculoskeletal issue amid the course of their work schedule, present study was a cross-sectional study completed among the physiotherapists in and around the Nellore town during 2010-2011.Methods: A two-page poll with shut finished inquiries is utilized as the information gathered technique. Inquiries included word related history of physiotherapists and musculoskeletal side effects, exceptional regions, assignments, occupation related danger elements, damage counteractive action methods, and reactions to harm. Poll distributed to 40 physiotherapists in and Nellore region, among them 28 respondents returned their inquire form. Of them 20 faced work related musculoskeletal discomfort (WRMSD). Then the data was collected and analyzed.Results: The result of present study showed high prevalence of injuries in physiotherapists. Prevalence of WRMSD's is higher among women (55%) compared to men (45%). The Physiotherapist respondents reported the highest level of work related musculoskeletal injury in the low back region. And next to the low back, most of the respondents reported the neck region and next to the neck, upper back, thorax, wrist and hands are affected.Conclusion: Training and continuous professional development, physiotherapist still report on a high incidence of work related injuries during their professional practice. Therefore in workplace specific interventions to reduce work related musculoskeletal discomfort (WRMSD) developed and adequate prevalence and appropriate managing strategies are to be recommended to minimize the work related musculoskeletal discomfort (WRMSDs) in the practice.